Revitalizing the Role of Islamic Religious Education (PAI) Teachers in Geopolitical Literacy as a Preventive Effort Against Radicalism and Intolerance in Schools - Mulyana, Yana (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Abstract This article discusses the importance of revitalizing the role of Islamic Religious Education (PAI) teachers in developing geopolitical literacy as a preventive strategy against radicalism and intolerance in schools. Revitalization is understood as an effort to restore the strategic functions of PAI teachers to make them more relevant to the challenges of a complex global era. Using a qualitative approach through library research, this article analyzes literature related to the integration of geopolitical issues into Islamic education. The findings show that PAI teachers play a vital role as value mediators, facilitators of intercultural dialogue, and agents of moderate character formation. Geopolitical literacy can serve as a contextual learning platform to instill universal Islamic values such as justice, peace, and compassion, which in turn can strengthen an inclusive and critical Islamic identity. Although challenges remain—such as limited teacher competence, curriculum constraints, and resistance from conservative circles—geopolitical literacy can still be integrated gradually and pedagogically. This study recommends strengthening educational policy, implementing teacher training on global issues, and promoting interdisciplinary collaboration as concrete steps toward building a contextual and transformative Islamic education ecosystem. Thus, Islamic education can become a frontline force in shaping a tolerant, peace-loving generation with a strong sense of geopolitical awareness.